Pergeseran Bahasa Kayo Pulau di Kota Jayapura yang Terancam Punah: Fakta, Sebab, Gejala, dan Strategi Pemeliharaannya - Anton Maturbongs (Balai Bahasa Provinsi Papua, 2019)
Based on some facts that found in Kayu Pulau village concerning of friction in Kayu Pulau language could be seen and observed in daily life of Kayu Pulau villagers. It cpould be seen in each society moment in have interaction or talk each other did not longer use Kayu Pulau language but Indonesian. Based on this fact, there was a friction of Kayu Pulau language to Indonesian itself.